Molecular Docking Study of Lycopene on Reducing the DNA-methyltransferase in Prostate Cancer - Sukirman, Annisa Muthiah (Bioinformatics and Biomedical Research Journal, 2018)
Lycopene is a member of a carotenoid family and is naturally abundant in tomatoes. The consumption of lycopene is already needed for human because it acts as an antioxidant, meanwhile, our body cannot produce that naturally. Previous studies have shown that there is an inverse relationship between dietary lycopene intake and the risk of PCa. However, the studied mechanism underlying how the lycopene affects or inhibit the control of cancer growth, in this case, is DNA-methyltransferase that can regulate the cancer genes, is still limited, and even absent. Motivated by that, a series of the method including preparation docking, molecular docking, and identifying the biological activity were done to study the mechanism of lycopene in reducing the DNMT. The result of lycopene-DNMT binding was compared with other known ligands that already known to bind the DNMT in its active site, which is SFG and SAH. The docking results showed that the binding affinity of lycopene and DNMT is lower than other ligands. The biological activity analysis also showed that lycopene is proven to have antioxidant activity, however, it still needs further study or experimental work to prove its ability for apoptosis agonist or as anti-proliferative disease because it is only computationally proven.